CHARACTERIZATION OF TRAUMATIC EVENTS ATTENDED BY THE FIRE DEPARTMENT OF THE CITY OF ITAPIRANGA - SC - Marta Kolhs; Jucimar Frigo; Grasiele Busnello; Dianâta Simone Welter (Revista de Pesquisa Cuidado é Fundamental Online)
Resumo